MANUSIA DAN PENDIDIKAN MENURUT PEMIKIRAN IBN KHALDUN DAN JOHN DEWEY - T. Saiful Akbar (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2015)
This study aims to understand the concept of human and Ibn Khaldun's ideas of education; to understand the concept of human and educational thought of John Dewey; to know the similarities and differences between the ideas of Ibn Khaldun and John Dewey on the concept of human and education. Various problems have been addressed through the library research method. The study produced several findings: First, human beings according to Ibn Khaldun as a creation of God with all the potential fitted to the five senses and intellect become intellect. The purpose of education opens the mind and maturity of the individual to the advancement of religious, industrial and social system. Material teaching is as educational planning. The method is to advocate phasing method, repetition, widya-tours and training (practice). Secondly, according to John Dewey man is a subject that has the ability, strength, personality, and existence who are capable of changing realities. The goal of education is only to gain happiness in the world life. The method of education is including problem solving, learning by doing and discipline. Third, the thought of Ibn Khaldun is much more religious because it is influenced by its control logic in religious knowledge, so that emphazises more on human spirituality in building civilization. While John Dewey is more radical and extreme, He proposed progressive education which strives against traditional teaching authority. Both Ibn KhaldÅ«n dan Dewey are arise from inhuman socio-cultural environment and recognize the existence of human existence with nature and humanity impulse.